Preparation of Robust Metal‐Free Magnetic Nanoemulsions Encapsulating Low‐Molecular‐Weight Nitroxide Radicals and Hydrophobic Drugs Directed Toward MRI‐Visible Targeted Delivery1. Issue 62 (12th October 2017) - Nagura, Kota; Takemoto, Yusa; Moronaga, Satori; Uchida, Yoshiaki; Shimono, Satoshi; Shiino, Akihiko; Tanigaki, Kenji; Amano, Tsukuru; Yoshino, Fumi; Noda, Yohei; Koizumi, Satoshi; Komatsu, Naoki; et al.
Abstract: With a view to developing a theranostic nanomedicine for targeted drug delivery systems visible by magnetic resonance (MR) imaging, robust metal‐free magnetic nanoemulsions (mean particle size less than 20 nm) consisting of a biocompatible surfactant and hydrophobic, low molecular weight 2, 2, 5‐trimethyl‐5‐(4‐alkoxy)phenylpyrrolidine‐ N ‐oxyl radicals were prepared in pH 7.4 phosphate‐buffered saline (PBS). The structure of the nanoemulsions was characterized by electron paramagnetic resonance spectroscopy, and dynamic light scattering and small‐angle neutron‐scattering measurements. The nanoemulsions showed high colloidal stability, low cytotoxicity, enough reduction resistance to excess ascorbic acid, and sufficient contrast enhancement in the proton longitudinal relaxation time ( T 1 ) weighted MR images in PBS in vitro (and preliminarily in vivo). Furthermore, the hydrophobic anticancer drug paclitaxel could be encapsulated inside the nanoparticles, and the resulting paclitaxel‐loaded nanoemulsions were efficiently incorporated into HeLa cells to suppress cell growth. Abstract : Look inside ! Metal‐free magnetic nanoemulsions encapsulating hydrophobic drugs (see scheme) were prepared with a view to develop theranostic nanomedicine for targeted drug‐delivery systems visible by magnetic resonance imaging.